2021
DOI: 10.1136/postgradmedj-2021-140824
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare distrust among hospitalised black patients during the COVID-19 pandemic

Abstract: Study purposeDistrust of the healthcare system is longstanding in the black community. This may especially threaten the health of the population when a highly contagious infection strikes. This study aims to compare COVID-19-related perspectives and behaviours between hospitalised black patients who trust versus distrust doctors and healthcare systems.Study designCross-sectional study at a tertiary care academic hospital in Baltimore, Maryland. Hospitalised adult black patients without a history of COVID-19 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Yet, in isolation, these efforts may not suffice. [33][34][35] Belief in whether the vaccine will work may be grounded in trust in the scientific community, a factor we found to be highly associated with vaccine acceptance. For the scientific community to engender trust, full disclosure of both benefits and risks of the vaccine is essential.…”
Section: Discussionmentioning
confidence: 89%
“…Yet, in isolation, these efforts may not suffice. [33][34][35] Belief in whether the vaccine will work may be grounded in trust in the scientific community, a factor we found to be highly associated with vaccine acceptance. For the scientific community to engender trust, full disclosure of both benefits and risks of the vaccine is essential.…”
Section: Discussionmentioning
confidence: 89%
“…27 The significant mistrust between minority populations and their healthcare was made more publically visible by the COVID-19 pandemic, which demonstrated in stark terms the enduring reality of the disparity in healthcare across US populations. 28,29 Within the literature, this mistrust has been confirmed among black patients and other communities of color. 12,[30][31][32] The aforementioned events highlight a more sinister process that may add to the disparities seen-racism.…”
Section: Resultsmentioning
confidence: 91%
“…Historically, the literature points to trials such as the Tuskegee Syphilis study as a core reason for mistrust among black patients and the healthcare system 27 . The significant mistrust between minority populations and their healthcare was made more publically visible by the COVID‐19 pandemic, which demonstrated in stark terms the enduring reality of the disparity in healthcare across US populations 28,29 . Within the literature, this mistrust has been confirmed among black patients and other communities of color 12,30–32 …”
Section: Discussionmentioning
confidence: 99%
“…A significant statistical disproportion was found with Blacks in our study making up 35.4% of the sample. Research has also shown that minorities are often, compared to Whites, at increased risk for chronic diseases [ 56 ]. Societal and systemic sources describe the unequal probability of having members of a specific racial group as a patient in our sample, perhaps due to strict patient selection or assessment of patient compliance, baseline health status, and comorbidities [ 55 ].…”
Section: Discussionmentioning
confidence: 99%